(untitled) (مجلة إحالات, 2026)
يتناول البحث المقامة الحلوانيّة لبديع الزمان الهمذاني في ظلّ عناصر عملية السرد، مقتصرة على عناصر الروي والشخصيات والمكان والزمان، هادفًا إلى الوقوف على الطريقة التي خدمت بها هذه العناصر موضوع المقامة، والرسالة التي أراد الهمذاني إيصالها في مقامته، وقد خلصت إلى نتيجة مفادها أنّ الهمذاني استطاع من خلال هذه العناصر أن يوصل النظرة السائدة في مجتمعه عن الإنسان، وعن إعلاء قيمة المال وذهاب قيمة الفكر، وتأكيده على أهميّة أخذ الأمور بجوهرها وعدم الانخداع بالظواهر. Abstract The research deals with the Hulwani maqamah of Badi al-Zaman al-Hamdhani in light of the elements of the narration process, limited to the elements of narration, characters, place and time. aiming to find out the way in which these elements served the subject of the maqamah, and the message that al-Hamdhani wanted to convey in his maqamah. Through these elements, he communicates the prevailing view in his society about the human being, about raising the value of money and departing the value of thought, and his emphasis on the importance of taking matters to their essence and not being deceived by phenomena.